Simulation RTK- GPS and Accelerometer Integration Monitoring Offshore Platform - Myint, K.C. (Institute of Electrical and Electronics Engineers Inc., 2020)
For the period of their operations, offshore platforms most withstand the expected environmental conditions of the site in which they are operated. The structural integrity of these platforms is assessed by measuring the response of the platforms from the environmental conditions. This study presented a method for measuring the displacement of offshore platforms using RTK-GPS and accelerometer. It is based on the real-time measurement of the three-dimensional displacement of a model platform by installing acceleration sensors and RTK-GPS apparatus. Results obtained from the measurement were processed to eliminate noise, and the displacements of the platform were obtained. It was found from the results of the displacements that both the accelerometer and the RTK-GPS results are in conformity. The maximum displacement of about 4mm was recorded for both methods. Â© 2020 IEEE.